Effect of Eu Doping on Structural, Optical and Magnetic Properties of BiFeO3 Materials - Viet Thang, Dao; Manh Hung, Nguyen; Phuong Thao, Nguyen; Cao Khang, Nguyen; Thi Mai Oanh, Le; Thi Cam Linh, Ngo; Dinh Tu, Bui (VNU Journal of Science: Mathematics - Physics; Vol 38 No 1DO - 10.25073/2588-1124/vnumap.4640, 2022)
Bi 1- x Eu x FeO 3 (BEFO) ( x = 0.00 ÷ 0.10) materials were prepared by sol-gel method. The crystal structural, Raman scattering, magnetic and optical properties of BEFO were investigated by X-ray diffraction (XRD), Raman scattering spectroscopy, magnetic hysteresis (M-H) loops and fluorescence spectroscopy (FL), respectively. Obtained results of the characterization showed that Eu-doping affected structural, optical and magnetic properties of BFO materials. All samples were crystallized in the rhombohedral structure with R 3C space group with crystal lattice parameters of a = 5.585 Å, c = 13.832 Å and the average crystal size of L XRD = 581 Å for BFO materials whereas the a , c and L XRD of Eu-doped samples decrease with the increasing of Eu 3+ concentration. The analysis result of Raman scattering spectroscopy showed that the position of the characteristic peak for Bi-O covalent bonds shifts toward higher frequency when Eu 3+ concentration increases, confirming the dopping substitution of Eu 3+ ions into Bi-sites. Fluorescence spectra showed the enhancement of characteristic emission peaks with the increase of Eu concentration. All samples exhibited weak ferromagnetic behaviour with saturation magnetization of M s = 0.006 emu/g and remnant magnetization of M r = 0.004 emu/g for BFO materials. The value of M s and M r of Eu-doped BFO increases compared to those of undoped-BFO. The origin of ferromagnetism and fluorescence improvement has been discussed.